2019
DOI: 10.1108/ijccsm-01-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and variability perceptions in Ga-Dikgale community in Limpopo Province, South Africa

Abstract: Purpose-Perceptions of climate change and its threats to rural communities are among major challenges faced by scientists around the world. A few studies prove that these communities are aware of change in climatic conditions and their impacts on people's livelihoods. Climate change is usually perceived as increasing warming days, erratic rainfall patterns, ecological variability, biological change and their adverse effects on human beings. This study aims to assess Ga-Dikgale community's perceptions on climat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…While farmers in the catchment observed the changes in climatic conditions of their area, not all of them take up remedial actions in response to these changes, due to barriers resulting from limited information about climate change and plausible adaptation options, financial constraints, lack of extension services and delayed farm inputs, among others. These barriers are, however, not unique to farmers in the Olifants catchment, as similar studies conducted by Gbetibouo (2009), Oduniyi et al (2019aOduniyi et al ( , 2019b and Chikosi et al (2019) in Limpopo Province, South Africa also reported similar barriers.…”
Section: Discussionsupporting
confidence: 57%
“…While farmers in the catchment observed the changes in climatic conditions of their area, not all of them take up remedial actions in response to these changes, due to barriers resulting from limited information about climate change and plausible adaptation options, financial constraints, lack of extension services and delayed farm inputs, among others. These barriers are, however, not unique to farmers in the Olifants catchment, as similar studies conducted by Gbetibouo (2009), Oduniyi et al (2019aOduniyi et al ( , 2019b and Chikosi et al (2019) in Limpopo Province, South Africa also reported similar barriers.…”
Section: Discussionsupporting
confidence: 57%
“…All over the world, small-scale farmers have shown a remarkable ability to act like entrepreneurs. Studies around the world have established that small-scale farmers have crafted better ways to organize their farms (Mugambiwa, 2018;Chikosi et al 2018;Gandure, Walker & Botha, 2013). It has emerged that smallscale farmers have long refrained from sticking to traditional crops for subsistence purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change–related disasters have escalated around the world, causing a serious threat to the existence of humans and their livelihoods (Mugambiwa & Tirivangasi 2017; Mugambiwa 2018; Tirivangasi 2018). Climate change affects agriculture, depletes water resources and impacts on food security (Chikosi, Mugambiwa, Tirivangasi & Rankoana 2018). Climate change, which is attributable to the natural climate cycle and human activities, has adversely affected agricultural productivity in Africa (Mugambiwa & Tirivangasi 2017; Ziervogel et al 2006).…”
Section: Introductionmentioning
confidence: 99%